2023
DOI: 10.1039/d2md00344a
|View full text |Cite
|
Sign up to set email alerts
|

Advances in research on 3C-like protease (3CLpro) inhibitors against SARS-CoV-2 since 2020

Abstract: COVID-19 caused by SARS-CoV-2 in late 2019 is still threatening global human health. Although some vaccines and drugs are available in market, controlling the spread of the SARS-CoV-2 virus remains...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 81 publications
0
14
0
Order By: Relevance
“…The 3CL pro , also known as Mpro, is an enzyme that plays a crucial role in the replication of several coronaviruses, including SARS-CoV-2 and FIPV. This enzyme is essential for viral replication because it cleaves the virus-produced polyproteins into functional mature proteins that are required for viral replication and assembly. , The SARS-CoV-2 3CL pro amino acid sequence was highly similar to that of FIPV (44% sequence identity) and had similar properties (97% match) (Figure a). FIPV infection of CRFK cells demonstrated that PQQ inhibits viral replication.…”
Section: Resultsmentioning
confidence: 99%
“…The 3CL pro , also known as Mpro, is an enzyme that plays a crucial role in the replication of several coronaviruses, including SARS-CoV-2 and FIPV. This enzyme is essential for viral replication because it cleaves the virus-produced polyproteins into functional mature proteins that are required for viral replication and assembly. , The SARS-CoV-2 3CL pro amino acid sequence was highly similar to that of FIPV (44% sequence identity) and had similar properties (97% match) (Figure a). FIPV infection of CRFK cells demonstrated that PQQ inhibits viral replication.…”
Section: Resultsmentioning
confidence: 99%
“…2) for the treatment in of COVID-19. This again signifies the importance of the fluorine atom (Assmus et al 2022;Ghosh et al 2022;Li et al 2022;Veeramani et al 2023;Chen et al 2023;Gahbauer et al 2023;Kneller et al 2022;Sasaki et al 2023).…”
Section: Fluorinated Drugs Recommended During the Covid-19 Pandemicmentioning
confidence: 90%
“…The team of Yang Haitao and Rao Zihe and that of Jiang Hualiang used computer-aided drug design to determine a potential inhibitor 13 (N3) (Figure 1(a)) for the main protease M pro of SARS-CoV-2, 41 which contains a Michael acceptor as a warhead and can effectively fight against a variety of coronaviruses, including SARS-CoV and the Middle East respiratory syndrome coronavirus (MERS-CoV). 42 indicating that these parts may not be the key to inhibiting the activity. The structure of these parts can be optimized to improve the efficacy and pharmacokinetic characteristics.…”
Section: Michael Acceptormentioning
confidence: 99%
“…The team of Yang Haitao and Rao Zihe and that of Jiang Hualiang used computer-aided drug design to determine a potential inhibitor 13 (N3) (Figure 1(a)) for the main protease M pro of SARS-CoV-2, 41 which contains a Michael acceptor as a warhead and can effectively fight against a variety of coronaviruses, including SARS-CoV and the Middle East respiratory syndrome coronavirus (MERS-CoV). 42 Compound 13 has antiviral effects in SARS-CoV-2-infected Vero cells (EC 50 = 16.77 μM). The crystal structure of the complex of SARS-CoV-2 M pro and inhibitor 13 was analyzed (PDB 6LU7).…”
Section: Targeted Inhibitors Of Sars-cov-2 Main Proteasementioning
confidence: 99%
See 1 more Smart Citation